2010
DOI: 10.1002/mds.22913
|View full text |Cite
|
Sign up to set email alerts
|

Myopathy causing camptocormia in idiopathic Parkinson's disease: A multidisciplinary approach

Abstract: Extreme forward flexion of the spine, named camptocormia (CC), and head drop syndrome (HD) may be among the most disabling symptoms in Parkinson's disease (PD). This study aims to eludicate the etiology of PD-associated CC and HD via a multidisciplinary approach (clinical examination, electromyography, MRI, genetic analysis, muscle morphology) centering on the histology of the paraspinal muscles. We studied 17 patients with the clinical diagnosis of PD and CC or head drop syndrome and six controls. We performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 34 publications
2
47
2
8
Order By: Relevance
“…68,70,71 Paraspinal muscle biopsies showed unspecific myopathic changes with type 1 fiber hypertrophy, type 2 fiber loss, loss of oxidative enzyme activity, and myofibrillar disorganization. 68 Similar myopathic changes have been found in patients with tenotomy, suggesting that they could be secondary to altered proprioception in PD and result from, rather than induce, chronic postural deviations.…”
Section: A S T R I O T O E T a Lmentioning
confidence: 99%
“…68,70,71 Paraspinal muscle biopsies showed unspecific myopathic changes with type 1 fiber hypertrophy, type 2 fiber loss, loss of oxidative enzyme activity, and myofibrillar disorganization. 68 Similar myopathic changes have been found in patients with tenotomy, suggesting that they could be secondary to altered proprioception in PD and result from, rather than induce, chronic postural deviations.…”
Section: A S T R I O T O E T a Lmentioning
confidence: 99%
“…The amorphous masses and myofibrillary disarrays stained positive for desmin and dystrophin, as with findings described in desmin-related myopathy or myofibrillar myopathy. Furthermore, they found unspecific myopathic changes in muscle biopsies including internalized nuclei, alterations in fiber size, and augmentation of connective tissue [24] . These findings are in general accordance with those of the above-named study [22] .…”
Section: Myopathy As a Cause Of CC And Dhs In Pdmentioning
confidence: 99%
“…Spuler et al [24] examined 17 patients, 13 of them with a myopathic pattern in electromyographic recordings. The authors found 'apparently folded proteins' in muscle biopsies suggesting the possibility of a myopathy induced by an accumulation of aggregated proteins.…”
Section: Myopathy As a Cause Of CC And Dhs In Pdmentioning
confidence: 99%
“…Only in single cases camptocormia may be the initial manifestation of Parkinson’s disease [30]. Camptocormia in Parkinson’s disease starts to develop between the age of 60 and 70 years [3] and the latency with which camptocormia occurs after onset of Parkinson’s disease is 5–10 years [1,31]. Camptocormia is most frequently found in patients with more severe Parkinson’s disease.…”
Section: Etiologymentioning
confidence: 99%
“…necrotizing myopathy, inflammatory myopathy, or mitochondrial myopathy [70]. Myopathic changes in patients with Parkinson’s disease include abnormal fiber size variation, increase of internal nuclei, increase of connective tissue, or myofiber disarray, or fatty degeneration [1,31]. In patients with advanced Parkinson’s disease and camptocormia muscle biopsy may show end-stage myopathy with autophagic vacuoles, chronic inflammatory myopathy, non-specific myopathic changes, or mitochondrial myopathy [33].…”
Section: Diagnosismentioning
confidence: 99%